Conflictos persistentes en una pareja parental después de un proceso de definición de custodia en una comisaría de Norte de Santander - Martínez Carrascal, Yuleidy (Universidad Antonio Nariño, 2022)
This research analyzes the persistent conflicts of a parental couple after the custody definition process at the Norte de Santander police station in Colombia. This analysis includes intergenerational factors, the construction of the couple's affective bond and the exercise of parenthood, the entire study is transversalized with the possibilities offered by family mediation as an alternative to resolve this type of situation. The methodological approach is qualitative and the method is a case study, the technique used is the free and in-depth interview that gives rise to the analytical categories and the interpretation of the information is produced, which reveals that a large part of the situations that motivate persistent conflicts are associated with the way in which the formation of the couple was structured and each evolutionary stage of the family was developed.